Aplikasi Konsep Green Design Berdasarkan Kriteria Penilaian Greenship Neighborhood Versi 1.0 pada Kawasan Terbangun Perumahan Grand City Balikpapan - Dewi, Tiara Rukmaya; Putra, Rullianor Syah; Jordan, Nadia Almira; Nabila, Nurhikma; Rahmadi, Danu (SPECTA Journal of Technology, 2024)
The relocation of the Indonesian new capital city to Ibu Kota Nusantara (IKN) has had an impact on rapid urban growth and development in the buffer area of Balikpapan City. The growth referred to is increasing area development, improving infrastructure, and increasing welfare. However, on the other hand, the transfer of IKN Nusantara could further increase the impact of global warming due to the high contribution of CO₂ emissions, especially those produced by buildings. Grand City Housing was chosen as the study location based on the green concept that has been implemented, the land area, and the availability of a master plan and environmental documents. The specific aim is to convey the green concept to Grand City Housing with the Greenship Neighborhood Assessment rating tool. This research method uses quantitative descriptive, namely that the results of the assessment of the research object are evaluated in the form of scores using the Greenship Neighborhood Assessment Version 1.0 rating tool. The results obtained were based on an assessment using Greenship Neighborhood version 1.0. The overall maximum score was 124, and the Grand City Housing area received a score of 28 with a weight of 22.4%, so this residential area did not meet any ranking. The highest score obtained was in the Movement and Connectivity category, with a score of 7 out of a maximum of 26. Meanwhile, the lowest scores were Building and Energy (BAE) and Development and Innovation (IFD), with an identical score of 2 out of a maximum score of 15 for BAE and 9 for IFD. Therefore, it is necessary to create a Grand City Housing environment that is suitable to live in, comfortable, and efficient in accordance with the Greenship Neighborhood Assessment Version 1.0 rating tools in urban environments.